Development of human white matter fiber pathways: From newborn to adult ages. Issue 50 (15th March 2016) - Cohen, Andrew H.; Wang, Rongpin; Wilkinson, Molly; MacDonald, Patrick; Lim, Ashley R.; Takahashi, Emi
Abstract: Major long‐range white matter pathways (cingulum, fornix, uncinate fasciculus [UF], inferior fronto‐occipital fasciculus [IFOF], inferior longitudinal fasciculus [ILF], thalamocortical [TC], and corpus callosal [CC] pathways) were identified in eighty‐three healthy humans ranging from newborn to adult ages. We tracked developmental changes using high‐angular resolution diffusion MR tractography. Fractional anisotropy (FA), apparent diffusion coefficient, number, length, and volume were measured in pathways in each subject. Newborns had fewer, and more sparse, pathways than those of the older subjects. FA, number, length, and volume of pathways gradually increased with age and reached a plateau between 3 and 5 years of age. Data were further analyzed by normalizing with mean adult values as well as with each subject's whole brain values. Comparing subjects of 3 years old and under to those over 3 years old, the studied pathways showed differential growth patterns. The CC, bilateral cingulum, bilateral TC, and the left IFOF pathways showed significant growth both in volume and length, while the bilateral fornix, bilateral ILF and bilateral UF showed significant growth only in volume. The TC and CC took similar growth patterns with the whole brain. FA values of the cingulum and IFOF, and the length of ILF showed leftward asymmetry. The fornix, ILF and UF occupied decreased space compared to the whole brain during development with higher FA values, likely corresponding to extensive maturation of the pathways compared to the mean whole brain maturation. We believe that the outcome of this study will provide an important database for future reference.